2009
DOI: 10.2139/ssrn.1553803
|View full text |Cite
|
Sign up to set email alerts
|

Social Expenditure and Poverty Reduction in the Eu15 and Other OECD Countries

Abstract: The European Union coordinates and encourages Member State actions to combat poverty, and to reform their social protection systems on the basis of policy exchanges and mutual learning ('best practices'). Some EU countries are more effective in poverty reduction than others. What can explain these variations in effectiveness? This paper analyzes the effectiveness of social transfers in alleviating poverty. We focus on EU15 countries, but also include other OECD countries in our analysis. We compare poverty rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In the case of Croatia, some of the factors contributing towards lower effectiveness include: a low level of means-tested social benefits (the World Bank, 2012), as well as little systematic monitoring of social assistance and benefits at national and local level (European Commission, 2013). Lower effect of the social protection system compared to the EU average, as indicated in other studies (Caminada and Goudswaard, 2009;Hermann et al, 2008) may also be seen as a result of the country's lower social spending. According to the ESSPROS 5 statistics (available only for Croatia and Serbia), social spending in Croatia in 2012 amounted to 20.6% of the country Gross Domestic Product (GDP), while Serbian social spending in 2010 (latest available data) amounted to 24.6% of its GDP (Eurostat, 2013).…”
Section: Policy Responses and Challenges Related To Poverty And Sociamentioning
confidence: 65%
“…In the case of Croatia, some of the factors contributing towards lower effectiveness include: a low level of means-tested social benefits (the World Bank, 2012), as well as little systematic monitoring of social assistance and benefits at national and local level (European Commission, 2013). Lower effect of the social protection system compared to the EU average, as indicated in other studies (Caminada and Goudswaard, 2009;Hermann et al, 2008) may also be seen as a result of the country's lower social spending. According to the ESSPROS 5 statistics (available only for Croatia and Serbia), social spending in Croatia in 2012 amounted to 20.6% of the country Gross Domestic Product (GDP), while Serbian social spending in 2010 (latest available data) amounted to 24.6% of its GDP (Eurostat, 2013).…”
Section: Policy Responses and Challenges Related To Poverty And Sociamentioning
confidence: 65%
“…There is also a large body of international comparative studies that looks at the relationship between social transfers and poverty Marlier et al, 1999;Atkinson, 2000;Caminada & Goudswaard, 2009;Bibi & Duclos, 2009;Eurostat, 2010). Most studies find that there is a strong relationship between the level of social expenditure and the poverty level.…”
Section: Social Transfers and Income Povertymentioning
confidence: 99%
“…A number of studies conducted over the past two decades have found that there is a strong negative correlation between poverty and social transfers. It means that countries with a higher level of social expenditure are likely to have lower poverty rates (Caminada & Goudswaard, 2009;Forster & d'Ercole, 2005;Anderson et al, 2018;Kim, 2000;Leventi et al, 2018). Public spending affects poverty reduction in several ways: it can raise the overall growth performance of the economy, and it can increase the chance of the poor to contribute to the growth process (mainly by strengthening human capabilities and reducing transaction costs).…”
Section: Relationship Between Social Transfers and Poverty Reductionmentioning
confidence: 99%
“…The effect may also differ according to the time period of analysis, since some types of spending have direct, immediate impacts on poverty (e.g., transfers and subsidies), while others only have more indirect, medium-term effects (e.g., health, education, and infrastructure spending) (Anderson et al, 2018). Caminada and Goudswaard (2009) found that the effect of public spending on poverty is less strong in EU countries compared to non-EU-15 countries. Celikay and Gumus (2017) found that in the short run there is a negative relationship between social expenditure and poverty, but in the long run there exists a positive correlation between social expenditure and poverty.…”
Section: Relationship Between Social Transfers and Poverty Reductionmentioning
confidence: 99%